"So you think I'm cute?": An observational study of adolescents' appearance evaluation in text messaging. Issue 5 (12th November 2021) - Burnell, Kaitlyn; Kurup, Allycen R.; Vollet, Justin W.; Underwood, Marion K.
Abstract: Adolescents are immersed in an appearance culture sustained by their peers, which includes being exposed to norms and expectations of physical attractiveness. A new avenue for transmitting these appearance messages may be digital technologies, including text messaging. Little is known about how appearance messages may naturalistically occur in adolescents' text communication. This study employed observational methods to quantitatively and qualitatively examine the transmission of appearance evaluative text messages in an ethnically diverse sample of U.S. 10th graders ( M age = 15.98, 47% girls). Quantitative descriptive analyses indicated that appearance evaluative texting was relatively infrequent but was still observed in text messages sent by over half of participants. These text messages were typically positive, but valence varied depending on toward whom the evaluation was targeted. Receiving these appearance evaluative messages was correlated with lower global self‐worth. A qualitative content analysis suggested that appearance evaluative messages serve to (a) provide a negative or positive assessment of the self, (b) transmit and elicit feedback, and (c) cultivate a culture within romantic partnerships in which appearance is valued. Findings are discussed in the context of existing digital theories (i.e., co‐construction theory, the transformation approach) and appearance‐oriented theories (i.e., objectification theory).